Postępowania prekwalifi kacyjne jako pierwszy etap udziału w aukcjach OZE - Trupkiewicz, Marcin (Studia Prawa Publicznego, 2019)
The paper describes the legal grounds of prequalifi cation proceedings allowing certain categories of energy producers to participate in the Polish auction system, and thus to create a new system responsible for supporting the development of renewable energy sources (RES). These procedures are of administrative proceedings character but are modifi ed by specifi c legal provisions under the RES regulations. The legislator diff erentiated between two types of these procedures. Although they diff er in specifi c legal provisions, they both pursue to achieve common targets that will subsequently contribute to a speedy development of the RES plants in Poland. Among the main objectives of the prequalifi cation proceeding, the necessity of the regulatory authority to obtain the basic information about the RES installation project must be mentioned. This information not only allows to check the legitimacy of the accession to the RES auctions system but also allows to check the investment documentation of the project, and consequently implement and start the RES installation on time as prescribed by the law. In the initial period, the measures taken by the RES are to be aimed at eliminating form the auction these energy producers who could theoretically win the RES auction but would not, due to legal, technical or fi nancial reasons manage to complete the investment (build and start up the RES installation) within the time prescribed. This would not only impede a competitive conduct of the RES auction but would also prevent realisation of the EU climate and energy policy due to the failure to produce enough electricity to meet the required volume contracted for each new RES installations according the RES auctions.